10Performance, Theatre, and Drama. (2nd June 2022) - Simpson, Hannah
Abstract: The first section of this review, 'Staging Reality', reads two monographs that grapple with large-scale thinking about how theatre and performance engage with various ideas of 'reality': Lindsay Brandon Hunter's exploration of performing 'the real' in theatre, television, and alternative-reality gaming in Playing Real: Mimesis, Media, and Mischief, and Bess Rowen's theorizing of 'affective stage directions' in The Lines Between the Lines: How Stage Directions Affect Embodiment . The second section, 'Politics and/of Performance', reviews two books with an explicit interest in the political as well as aesthetic dimensions of performance: Tiziana Morosetti and Osita Okagbue's edited volume The Palgrave Handbook of Theatre and Race, and Jon Venn's Madness in Contemporary British Theatre: Resistances and Representations . The final section shifts to monographs that structure their enquiry around a specific figure: the playwright Jez Butterworth, in the case of Sean McEvoy's Class, Culture and Tragedy in the Plays of Jez Butterworth, and the biblical figure of Salomé, in the case of Megan Girdwood's Modernism and the Choreographic Imagination: Salome's Dance after 1890 .